Tasha : a son's memoir - Morton, Brian, 1955- (Avid Reader Press, an imprint of Simon & Schuster, Inc., 2022)
"Acclaimed novelist Brian Morton delivers a moving, darkly funny memoir of his mother's vibrant life and the many ways in which their tight but turbulent relationship was refashioned in her twilight years. Tasha Morton is a force of nature: a brilliant educator who's left her mark on generations of students -- and also a whirlwind of a mother: intrusive, chaotic, oppressively devoted and irrepressible. For decades, her son, Brian, has kept her at a self-protective distance, but when her health begins to fail, he knows it's time to assume responsibility for her care. Even so, he's not prepared for what awaits him, as her refusal to accept her own fragility leads to a series of epic outbursts and altercations that are sometimes frightening, sometimes wildly comic, and sometimes both. Clear-eyed, loving and brimming with dark humor, Tasha is both a vivid account of an unforgettable woman and a stark look at the impossible task of caring for an elderly parent in a country whose unofficial motto is "you're on your own." Turning his novelist's eye on his own life, Brian Morton lays bare the treacherous business at the heart of every family -- the business of trying to honor ourselves without forsaking our parents, and our parents , and our parents without forsaking ourselves." - jacket.